A Model of Retention and Remediation for Online Counselor Education - Colleen M Grunhaus; Matthew Lyons (Teaching and Supervision in Counseling, 2024)
Online counseling programs experience unique retention and gatekeeping challenges. Increased isolation and personal adversities are common factors associated with attrition for online students; and broad-access admission policies of online counseling programs often lead to increased gatekeeping concerns postadmission. Counseling programs develop policies and procedures related to retention, remediation, and dismissal, but extant models of remediation do not also address student retention or the unique challenges of online counselor education. We present a model, The Retention and Remediation Model for Online Counselor Education, that demonstrates a comprehensive policy for retention, remediation, and dismissal in online counseling programs through a three-prong approach that includes recognizing student achievements (compliment referrals), connecting at-risk students to resources (connect referrals), and remediating students’ academic, clinical, and dispositional concerns (concern referrals). A case example is presented that demonstrates the implementation of connect and concern referrals, and implications related to triangulation, cultural sensitivity, and cyberincivility are discussed.
Keywords: Remediation; Gatekeeping; Retention; Online Counselor Education; Counselors in Training